A conserved acidic motif is crucial for enzymatic activity of protein o-mannosyltransferases - Lommel, Mark; Schott, Andrea; Strahl, Sabine (The journal of biological chemistry, 2011)
Protein O-mannosylation is an essential modification in fungi and mammals. It is initiated at the endoplasmic reticulum by a conserved family of dolichyl phosphate mannose-dependent protein O-mannosyltransferases (PMTs). PMTs are integral membrane proteins with two hydrophilic loops (loops 1 and 5) facing the endoplasmic reticulum lumen. Formation of dimeric PMT complexes is crucial for mannosyltransferase activity, but the direct cause is not known to date. In bakers' yeast, O-mannosylation is catalyzed largely by heterodimeric Pmt1p-Pmt2p and homodimeric Pmt4p complexes. To further characterize Pmt1p-Pmt2p complexes, we developed a photoaffinity probe based on the artificial mannosyl acceptor substrate Tyr-Ala-Thr-Ala-Val. The photoreactive probe was preferentially cross-linked to Pmt1p, and deletion of the loop 1 (but not loop 5) region abolished this interaction. Analysis of Pmt1p loop 1 mutants revealed that especially Glu-78 is crucial for binding of the photoreactive probe. Glu-78 belongs to an Asp-Glu motif that is highly conserved among PMTs. We further demonstrate that single amino acid substitutions in this motif completely abolish activity of Pmt4p complexes. In contrast, both acidic residues need to be exchanged to eliminate activity of Pmt1p-Pmt2p complexes. On the basis of our data, we propose that the loop 1 regions of dimeric complexes form part of the catalytic site.